Locked down-locked in: experiences of families of young children with autism spectrum disorders in Delhi, India - Kaur, Abhipreet; Lall, Gitanjali; Abhilashi, Minal; Naithani, Lavangi; Verma, Mamta; Roy, Reetabrata; Juneja, Monica; Gulati, Sheffali; Taylor, Carol; Leadbitter, Kathy; Patel, Vikram; Green, Jonathan; et al. (Frontiers in Public Health, 2024)
The onset of the COVID-19 pandemic and subsequent lockdowns in March 2020 disrupted the lives of families across India. The lockdown related restrictions brought forth a multitude of challenges including loss of employment, social isolation, school closures and financial burdens. Specifically, it also resulted in the restriction of health-care services for children with neurodevelopmental disabilities. This qualitative study was conducted as a part of a larger trial in India to understand the experiences of families of young children with autism during the pandemic. In-depth interviews were carried out with 14 caregivers residing in New Delhi, India. Our findings identified pandemic and lockdown's universal impacts on family life and financial stability stemming from job loss, business closure, and salary deductions, affecting quality of life of families. Furthermore, COVID-19 pandemic's impact on specifically autistic children was evident through limited access to essential services and financial challenges related service interruptions even after resumption of services. The lockdown's novelty also affected children's behavior, with both challenging behavioral changes and positive impacts. Primary caregivers, predominantly mothers, assumed additional responsibilities in household tasks, schooling, and therapy administration. While these experiences were universally experienced, these notably improved outcomes for autistic children. Despite challenges, parents expressed gratitude for their family's safety and well-being during the difficult time. These findings inform service provision for vulnerable families and offer implications for designing interventions such as credit schemes for families, guidance and resources for establishing and maintaining routines of children with autism, adopting flexible and adaptable approach to service delivery, and special provisions for children with autism to be able to maintain their routines outside of home. Furthermore, the study highlights the need for comprehensive support, including educational resources and stress management counselling to empower parents in supporting essential care and routines for their children during such unprecedented times.